Strategies for Implementing Group Mental Health Interventions in a VA Community Living Center. Issue 5 (20th October 2022) - Strong, Jessica V.; Plys, Evan; Hartmann, Christine W.; Hinrichs, Kate L. M.; McCullough, Megan
ABSTRACT: Objectives : Group mental health interventions are difficult to implement into rehabilitation facilities, but no one has studied the specific barriers. This mixed-methods project systematically examined the implementation of a mental health (MH) group intervention in a VA community living center (CLC) for residents on subacute rehabilitation units, using the Promoting Action on Research Implementation in Health Services (PARIHS) implementation framework. Methods : We implemented a group MH intervention, tracking team referrals, attendance rates, and reasons for declining to participate. We conducted qualitative interviews with attendees. Results : Individual barriers to attendance included acute illness (n = 67, 20%), attitudes toward MH ( n = 50; 15%), and perceived busyness ( n = 19; 6%). Facility barriers included competing appointments ( n = 69; 21%). Interviews demonstrated challenges to implementation, including stigma toward mental health (Theme: Challenges and Supports to Implementation). Attendees found the group relatable, and noted that both positive and negative group dynamics contributed to their experience (Themes: Content Relevance and Group Dynamics). Conclusions : The results provide insight into implementing a group MH treatment into the CLC setting, with implications for the MH care of older adults residing in CLCs. Clinical Implications : 1) Group leaders should consider matching attendees for ability levels (physical or cognitive). 2) At the facility level, leaders may take steps to address stigma toward MH by adopting approaches (e.g., music) or framing MH issues (e.g., use of language) in a way that is approachable. 3) Modifiable barriers at the individual and facility level could be addressed to encourage ease of implementation.